Unveiling The Teaching of Reading Skills at the Senior High Level: Perspectives from General Santos City Schools - Rebucias, Andreve John L.; Mangaron, Rossel A. (Future Science / FSH-PH Publications, 2024)
Several data from national and international tests have revealed the continued and unfortunate decline in reading proficiency among young Filipinos. Although many studies have already investigated this matter, few have dared to explore how higher levels of basic education are addressing the issue and preparing young Filipinos to be proficient readers for college. Hence, this qualitative research explored the teaching of reading skills at the senior high level and developed a survey questionnaire based on the themes that emerged from the interview data. Participants in the study included 14 teachers from three prominent schools in General Santos City. With a phenomenological approach, the researcher conducted key informant interviews using a developed and validated semi-structured interview schedule. The qualitative findings revealed three main dominant themes namely; the encountered challenges of the teachers, their practice of certain approaches and strategies in teaching reading skills, and their implementation of several intervention and remediation programs. The Dominant themes, emergent themes, subthemes, and codes, were then used as the basis for developing a survey questionnaire that had undergone reliability and validity testing. With the results, the research recommends revisiting the senior high curriculum and including intervention or remediation programs to aid struggling senior high readers and strengthen the reading skills of senior high students in general. Furthermore, the researcher encourages using the developed survey questionnaire to investigate the phenomenon further in a more generalizable population.